THE INFLUENCE OF HUMAN RESOURCES QUALITY, MOTIVATION AND COMPENSATION ON EMPLOYEE PERFORMANCE IN ENREKANG SUB-DISTRICT OFFICE, ENREKANG DISTRICT - Iman Arifin; Nurdin Brasit; Fauziah Umar (The Scientia Law and Economics Review, 2023)
FAITH ARIFIN.The Effect of Quality of Human Resources (HR), Motivation and Compensation on Employee Performance at the District Office of Enrekang DistrictEnrekang . This study aims to determine: (1) the effect of the quality of human resources, Partial and Simultaneous Motivation and Compensation for employee performance at the Enrekang sub-district office, Enrekang district.This research was conducted at the Enrekang sub-district office, Enrekang Regency, which is located at Jalan Jendral Sudirman No.25, Batili. This research method is a quantitative descriptive approach. Data collection techniques using questionnaires and observation methods. Data analysis in this study used validation test techniques, reliability and multiple linear regression analysis using the SPSS for Windows version 25 application, with a total sample of 23 respondents. The results of this study indicate that: 1) The quality of human resources has a partial effect on employee performance at the Enrekang sub-district office, Enrekang Regency which is characterized by a t count value that is greater than t table, namely 2.217 > 2.093 . 2) Motivation has a partial effect on employee performance at the Enrekang sub-district office, Enrekang Regency which is characterized by a t count value that is greater than t table, namely 2.834 > 2.093. 3) Compensation has a partial effect on employee performance at the Enrekang sub-district office, Enrekang Regency which is characterized by a t count value that is greater than t table, namely 5.445 > 2.093 . 4) Quality of Human Resources, Motivation and Compensation simultaneously influence employee performance at the Enrekang sub-district office